Faktor-faktor yang berkaitan dengan pemindahan latihan teknologi maklumat di Majlis Bandaraya Johor Bahru - A. Wahab, Nurnabila (2012)
Development of information technology is now seen in all matters of competition. Smart organizations leverage all existing technologies and future opportunities that will continue to compete and strengthen their position in the economic environment that is competitive. This resulted in many organizations have been providing training programs that lead to knowledge and IT skills. Accordingly, this thesis studies conducted to determine the level, the relationship and the factors that most affect the transfer of IT training in Majlis Bandaraya Johor Bahru (MBJB). This study uses quantitative methods in which samples were 108 MBJB employees. SPSS version 16.0 was used for quantitative data analysis using frequency distribution and mean scores, Pearson correlation and multiple regressions using the survey questionnaire. The results showed that the overall level of IT training transfer at a high level and there is a relationship between the factors associated with the transfer of IT training with each dimension of the transfer of IT training, while, there was significant relationship on a high level between transfer factors of IT training with the transfer of IT training among MBJB employees. The findings of this study also showed that most affect the transfer of IT training among MBJB employees is a trainee characteristics factor in which these factors play an important role to enable the transfer of IT training occur effectively.